Peran Komunitas Saujana Bentala Program Sisir Aksara dalam Meningkatkan Literasi Baca dan Tulis di Alun-Alun Kabupaten Karawang - Harahap, Farelsada Athaya; Musa, Safuri; Hidayat, Dayat (Innovative: Journal Of Social Science Research, 2025)
This study aims to describe the role of the Saujana Bentala Community through the Sisir Aksara Program in enhancing reading and writing literacy among the community at Alun-Alun Karawang Regency and to evaluate the literacy improvement outcomes achieved. The low level of reading and writing literacy in Indonesia, especially at the local level, remains a significant challenge influenced by limited access to reading materials, lack of supportive public spaces for learning, and insufficient inclusive and sustainable literacy activities. The Saujana Bentala Community emerges as a grassroots alternative with a participatory approach actively involving the community in literacy programs. This qualitative case study involved key informants including the Community Chairperson, the Karawang Regency Tourism and Cultural Office, community administrators, and program participants. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted systematically through data reduction, data presentation, and conclusion verification. Findings indicate that the Saujana Bentala Community plays a crucial role in creating a safe and inclusive space for members to express their literacy skills, serving as a platform for information exchange, community identity affirmation, and social strengthening among members. The Sisir Aksara Program successfully enhances community access to reading materials, organizes various interactive literacy activities such as book discussions and writing workshops, and builds partnerships to expand the program's reach and quality. Moreover, the program contributes to behavioral changes by habituating literacy practices, improving quality of life through writing skill development, and raising awareness of rights and responsibilities in sustaining literacy activities. Thus, the program not only improves technical literacy skills but also strengthens the social and cultural dimensions of community literacy in a sustainable manner. Keywords: literacy, community, Saujana Bentala, Sisir Aksara, case study, Alun-Alun Karawang Regency